Using training journals to increase motivation and performance - Milbrath, M. J.; Humble, K. W. (Olympic & Paralympic Coach, 2014)
Continual improvement in sport requires extensive time commitments that extend beyond training sessions themselves. The requirement for focus not only during training, but on maintenance of a healthy lifestyle, can demand an extreme amount of attention to detail on a daily basis. As an athlete becomes increasingly accomplished, the number of factors that are measured and which must be accounted for also increase. Training journals have long been accepted as a method to record the details and rigors of training and are thought to aid in the improvement of athletes. But how does it do this? More importantly, how can you insure that your athlete can improve from using a training journal? This article proposes a method that coaches can use to optimize an athletic environment through use of training journals. The purpose of keeping a training journal is two-fold - increase intrinsic motivation, and enable athletes to take ownership over their training, both of which are known to increase performance in athletes (Barry J. Zimmerman & Kitsantas, 2005a, 2005b).The framework is presented using wording specific to endurance runners; however, it can be adjusted to suit athletes of different sports by changing objectives and prompting questions that are addressed in this article.